TDP43 Exacerbates Atherosclerosis Progression by Promoting Inflammation and Lipid Uptake of Macrophages - Huangfu, Ning; Wang, Yong; Xu, Zhenyu; Zheng, Wenyuan; Tao, Chunlan; Li, Zhenwei; Hu, Yewen; Chen, Xiaomin (Frontiers in Cell and Developmental Biology, 2021)
Objective Atherosclerosis (AS), characterized by cholesterol overloaded-macrophages accumulation and plaque formation in blood vessels, is the major cause of cardiovascular disease. Transactive response DNA-binding protein∼43 kDa (TDP43) has recently been identified as an independent driver of neurodegenerative diseases through triggering inflammatory response. This study investigated whether TDP43 is involved in AS development, especially in macrophages-mediated-foam cell formation and inflammatory responses. Methods Transactive response DNA-binding protein∼43 kDa expressions in oxidized low-density lipoprotein (oxLDL)-treated macrophages and peripheral blood mononuclear cells (PBMCs) from patients with coronary artery disease (CAD) were detected by real time-polymerase chain reaction (RT-PCR), Western blot, and immunofluorescence. Gene gain or loss of function was used to investigate the effects of TDP43 on macrophages-mediated lipid untake and inflammation with ELISA, protein immunoprecipitation, RT-PCR, Western blot, and immunofluorescence. Macrophage TDP43 specific knockout mice with ApoE–/– background were fed with western diet for 12 weeks to establish AS model, and used to explore the role of TDP43 on AS progression. Results Transactive response DNA-binding protein∼43 kDa expression increases in oxLDL-treated macrophages and PBMCs from patients with CAD. Furthermore, we find that TDP43 promotes activation of NF-κB to increase inflammatory factor expression in macrophages through triggering mitochondrial DNA release to activate cGAS-STING signaling. Moreover, TDP43 strengthens lipid uptake of macrophages through regulating β-catenin and PPAR-γ complex to promote scavenger receptor gene CD36 transcription. Finally, using macrophage TDP43 specific knockout mice with ApoE–/– background fed with western diet for 12 weeks to establish AS model, we find that specific knockout of TDP43 in macrophages obviously alleviates western diet-induced AS progression in mice. Conclusions Transactive response DNA-binding protein∼43 kDa exacerbates atherosclerosis progression by promoting inflammation and lipid uptake of macrophages, suggesting TDP43 as a potential target for developing atherosclerotic drug.